Design of Nickel-Cobalt-Ruthenium multi-principal element alloys. (1st August 2020) - Charpagne, M.A.; Vamsi, K.V.; Eggeler, Y.M.; Murray, S.P.; Frey, C.; Kolli, S.K.; Pollock, T.M.
Abstract: The possibility of designing multi-principal element alloys in the Ni-Co-Ru system is investigated by first-principles and experimental means. A high-throughput first-principles approach is employed to probe the effect of composition on planar fault energies. Of most interest, a FCC alloy, Ni 40 Co 40 Ru 20, exhibits a high room temperature strength compared to existing nickel-containing solid solution FCC high entropy alloys. The presence of Ru imparts the alloy with unique properties. First, the low stacking fault energy provides a low critical resolved shear stress for twinning, allowing a TWIP effect. Second, the high lattice friction and the associated high yield strength enables the critical resolved shear stress for twinning to be reached at low strains at room temperature, resulting in the formation of a dense network of planar defects for increased work hardening. A TRIP effect is also observed at higher strains at room temperature. Graphical abstract: